Development of Local Wisdom-Based Student Worksheets: Needs Analysis in Elementary Schools in Situbondo Regency - Nuris Hidayat; Dewa Bagus Sanjaya; I Gede Margunayasa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Rapid advances in technology and science can be a challenge in maintaining local wisdom. Education is one alternative way to overcome these problems. Educational innovations carried out by teachers in learning activities can integrate local wisdom into teaching materials such as Student Worksheets. This study aims to describe the analysis of local wisdom-based Student Worksheets in Situbondo Regency, which includes the curriculum analysis process. These mapping materials will be integrated with local wisdom culture, and materials will be determined based on learning achievements and indicators. This study uses a qualitative descriptive approach with teachers in Situbondo Regency as research subjects. The sampling technique uses purposive sampling. Data collection uses observation, documentation, and interviews. The study was conducted by analyzing the curriculum, focusing on Student Worksheets, mapping materials, determining Student Worksheets, and making Student Worksheets. The results of this study show that there is a need for the development of local wisdom-based Student Worksheets so that students have knowledge about culture and values ​​that can be taken. Furthermore, this study recommends that teachers develop Student Worksheets by incorporating local wisdom values ​​from their respective regions.